Design, synthesis, and micellar properties of bile acid dimers and oligomers linked with a 1,2,3-triazole ring - Aher, Nilkanth G.; Pore, Vandana S.; Patil, Sachin P. (Tetrahedron, 2007)
1,3-Dipolar cycloaddition of propargyl esters of bile acids to azide group attached at different positions of bile acids gave dimers, trimer, and tetramer linked with 1,2,3-triazole. These dimeric and oligomeric structures were able to solubilize hydrophilic dye-cresol red, in nonpolar solvent. (c) 2007 Elsevier Ltd. All rights reserved.